Assessing cities growth-degrowth pulsing by emergy and fractals: A methodological proposal. (June 2021) - Agostinho, Feni; Costa, Marcio; Coscieme, Luca; Almeida, Cecília M.V.B.; Giannetti, Biagio F.
Abstract: As a powerful tool for assessing cities development, the emergy synthesis considers the energy quality concept, which allows it to quantify all the effort provided by nature in providing resources, however, it usually demands a huge amount of data and still lacks a complete and updated database for long-term studies. Cities seem to develop according to fractals, building up parts that resemble the whole, which is also relevant in emergy theory and observable through night-time lights from cities that are used to investigate how energy use distributes as cities change. This work proposes an alternative method for estimating the fractal dimension and non-renewable empower density (NRED) of cities from satellite night-time images and assess the relationship between them. Nine cities in Brazil, selected through a cluster analysis, were considered as a case study. Results show a strong positive correlation (0.94 for Pearson index) between fractals and NRED, which can be of help in estimating each other for further studies. The method proposed is time and cost effective when compared to previously used methods based on red/blue/green (RBG) satellite images, representing a potential alternative for assessing urban expansion in spatiotemporal models and assessing cities limits to growth. Highlights: Nighttime satellite imagery is used as a proxy to estimate cities' fractal and emergy. Urban expansion in spatiotemporal models is used to assess cities limits to growth. There is strong positive correlation between fractal and emergy. Cities evaluated are all at the growing stage.